A systematic review on SARS-CoV-2 remission: an emerging challenge for its management, treatment, immunization strategies, and post-treatment guidelines. (January 2022) - Joshi, R.; Singla, R.; Mishra, A.; Kumar, M.; Singh, R.S.; Singh, A.; Bansal, S.; Sharma, A.R.; Sarma, P.; Prakash, A.; Medhi, B.
Abstract: The COVID-19 disease caused by severe acute respiratory syndrome coronavirus -2 (SARS-CoV-2) has posed as a major health concern for people all across the globe. Along with the increasing confirmed patients being readmitted with complaints for fever, cough, cold, the effective monitoring of 'relapse' of the SARS-CoV-2 virus in the previously discharged patients have become the next area of focus. However, availability of limited data on reactivation of SARS-CoV-2 makes the disease prognosis as well as the effective control of re-infection an immense challenge. Prompted by these challenges, we assessed the possibility of re-infection in discharged patients and the risk of the transmission, proficiency of RT-PCR results and approximate period required for the quarantine, and the real challenges for the development of vaccine. In the present review, the published literature on all the possible cases of re-infection from February to July were reported, thereby selected 142 studies from a hub of overall 669 studies after full text screening. The incomplete virus clearance, poor sensitivity of the present diagnostic testing, emergence of mutant strains, insufficient mucus collection from the throat swab etc., are some of the possible causes of re-infection. The new protocols for management of COVID-19 discharged patients should be revised in the guidelines.